초밀집 이종 이동 통신망을 위한 적응형 셀 선택 기법 - 조정연; 반태원; 정방철; Jo, Jung-Yeon; Ban, Tae-Won; Jung, Bang Chul (한국정보통신학회논문지, 2015)
As smart-phones become popular, mobile data traffic has been dramatically increasing and intensive researches on the next-generation mobile communication network is in progress to meet the increasing demand for mobile data traffic. In particular, heterogeneous network (HetNet) is attracting much interest because it can significantly enhance the network capacity by increasing the spatial reuse with macro and small cells. In the HetNet, we have several problems such as load imbalance and interference because of the difference in transmit power between macro and small cells and cell range expansion (CRE) can mitigate the problems. In this paper, we propose a new cell selection scheme with adaptive cell range expansion bias (CREB) for ultra dense HetNet and we analyze the performance of the proposed scheme in terms of average cell transmission rate through system-level simulations and compare it with those of other schemes. 스마트폰의 대중화에 따라 무선 데이터 트래픽이 기하급수적으로 증가하고 있으며, 이러한 데이터 트래픽을 원활히 수용하기 위하여 차세대 이동통신 네트워크에 대한 연구가 활발히 진행 중이다. 특히, 매크로 셀과 소형 셀을 활용하여 공간 재활용성을 높임으로써 네트워크 용량을 획기적으로 개선할 수 있는 이종 이동 통신망이 많은 관심을 끌고 있다. 이종 이동 통신망에서는 매크로 기지국과 소형 기지국 간의 송신전력의 차이로 인하여 부하 불균형과 간섭등의 문제가 발생하며, 이를 해결하기 위하여 cell range expansion (CRE) 기술을 활용한다. 본 논문에서는, 초밀집 이종 이동 통신망 에서 CRE bias (CREB)를 적응적으로 적용하는 새로운 셀 선택 방식을 제안하고 시스템 레벨 시뮬레이션을 통하여 셀 평균 전송률을 분석하고, 기존의 셀 선택 방식과 비교 한다.